Formation and evolution of Al/steel interface structure in composite casting - Cao, Lei; Wang, Yu; Zang, Xi-min; Li, Yang; Wang, Guo-cheng; Xiao, Yuan-you (China foundry, 2024)
Al/steel composite materials were prepared using liquid-solid composite casting method, with aluminum as the liquid and 45 steel rods as the solid. The key factors affecting the formation and evolution of intermetallic compounds at the Al/steel reaction interface were studied. Results show that the defects present in the intermetallic compounds prepared at a liquid temperature of 900 °C and a holding time of 20 s are the least. The average hardness of Fe 2 Al 5 phase is 3 times higher than that of 45 steel and more than 7 times higher than that of pure aluminum. The average shear strength of the sample obtained through air cooling is higher than that of water cooling, and Fe 2 Al 5 phase is the main reason for the brittle fracture of the sample. The activation energy calculation of intermetallic compounds reveals that Fe 2 Al 5 is easy to grow up than FeAl 3 phase under air cooling conditions, and FeAl 3 is easy to grow up than Fe 2 Al 5 phase under water cooling conditions. This work offers assistance in studying the formation of intermetallic compounds during composite casting processes.